Enhancing quality and climate resilient traits in vegetatively propagated polyploids: transgenic and genome editing advancements, challenges and future directions - Sakthivel, Surya Krishna; Vennapusa, Amaranatha Reddy; Melmaiee, Kalpalatha (Frontiers in Genetics, 2025)
Vegetatively propagated polyploid crops such as potato, strawberry, sugarcane, and banana play a crucial role in global agriculture by meeting essential nutritional and food demands. The quality of the economically important traits in these crops is significantly affected by global climate change. However, their complex genomes and clonal propagation nature pose significant challenges for traditional breeding to improve quality and climate-resilient traits. Transgenics and genome editing offer promising solutions in crop improvement to enhance yield, quality, and biotic and abiotic stress tolerance. Despite these advancements, several challenges persist, such as a lack of genotype-independent transformation protocols, random transgene integration, unintended mutations, and somaclonal variation. The complexity of polyploid genomes also necessitates optimizing editing tools to improve precision and efficiency. Regulatory hurdles and public acceptance further influence the commercial success of genetically engineered crops. Employing efficient transgene-free genome-editing platforms can help to overcome the regulatory hurdles and accelerate breeding even in heterozygous backgrounds. This review reports the recent progress, obstacles, and prospects of transgenics and genome editing in vegetatively propagated crops, namely, potato, strawberry, banana, and sugarcane, focusing on quality and climate-resilient traits and methods to address technical challenges and navigate regulatory hurdles. The reported advancements in genetic engineering approaches for addressing challenges in improving the vegetatively propagated polyploid crops have tremendous potential in ensuring food security and agricultural sustainability in the face of climate change.